Pointing to Kinesthetic Targets in Space - Baud-Bovy, Gabriel (J Neurosci, 1998)
An experiment investigated in human adults the sensorimotor transformation involved in pointing to a spatial target identified previously by kinesthetic cues. In the “locating phase,” a computer-controlled mechanical arm guided the left [condition LR (left–right)] or right [condition RR (right–right)] finger of the blindfolded participant to one of 27 target positions. In the subsequent “pointing phase,” the participant tried to reach the same position with the right finger. The final finger position and the posture of the arm were measured in both conditions. Constant errors were large but consistent and remarkably similar across conditions, suggesting that, whatever the locating hand, target position is coded in an extrinsic frame of reference (target position hypothesis). The main difference between the same-hand (RR) and different-hand (LR) conditions was a symmetric shift of the pattern of endpoints with respect to the midsagittal plane. This effect was modeled accurately by assuming a systematic bias in the perception of the postural angles of the locating arm. The analysis of the variable errors indicated that target position is represented internally in a spherical coordinate system centered on the shoulder of the pointing arm and that the main source of variability is within the planning stage of the pointing movement. Locating and pointing postures depended systematically on target position. We tested qualitatively the hypothesis that the selection of both postures (inverse kinematic problem) is constrained by a minimum-distance principle. In condition RR, pointing posture depended also on the locating posture, implying the presence of a memory trace of the previous movement. A scheme is suggested to accommodate the results within an extended version of the target position hypothesis.